Cultural Implications of Citizenship for Creating a Democratic Young Generation - Azahra Sani, Adinda Salwa (PT. Berlian Pustaka Indonesia, 2023)
Citizenship culture is a culture that is the foundation of citizenship whose contents are about a set of ideas that can be realized effectively for cultural reception whose purpose is to form citizen identities here. Citizenship culture is very important for developing civics education. This is due to forming citizen identities, especially in the millennial generation where the identity in question is their identity as Indonesian citizens. Through Civics learning which already contains elements of civic culture, of course, the millennial generation will be able to think critically, rationally and creatively to examine various citizenship issues and actively contribute to various community and state activities. The real form resulting from the reactualization of civic culture is the establishment of learning in the form of anti-corruption education. Besides that, it is hoped that the characters of the younger generation will grow and develop positively and democratically in order to be able to compete with other nations without forgetting national identity with elements of technological development in it.